Penerapan Algoritme Genetika Pada Kasus Optimasi Penentuan Bibit dan Pemerataan Subsidi pupuk (Studi Kasus: Desa Pandansari, Kabupaten Kediri) - Erlyan Eka Pratiwi; Agus Wahyu Widodo; Wayan Firdaus Mahmudy (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Equity in the distribution of subsidized fertilizer has several constraints. Based on a survey of equal distribution of seed and fertilizer subsidy at farmer group of Pandansari Village of Kediri Regency, several equality obstacles are that most farmers have no basis and proper calculation in buying fertilizer subsidy based on nutrition requirement of planted seeds. So that resulted in farmers only buy the type of fertilizer with the same composition when different plant varieties that cause less than maximum yield. Besides also if the composition of fertilizer not in accordance with the varieties then the amount of fertilizer in the warehouse will be shortages and excess. To solve the problem used Genetic Algorithm method. The algorithm parameters used in rice plants are population as much as 220, generation as much as 1100, crossover rate 0,8 and mutation rate 0,2 whereas in corn plant population as much as 320, generation 1250, crossover rate 0,8 and crossover rate 0 , 2. The average percentage difference in value generated by genetic algorithm and fertilizer in warehouses on rice plant is 9,873% while in corn plants yield difference of mean percentage between fertilizer in warehouse and genetic algorithm equal to 24,882%. Solution The composition of fertilizers produced by genetic algorithms can be ascertained that the nutrients needed by plants are met so that the yield can increase.